2003
DOI: 10.1358/dot.2003.39.5.740221
|View full text |Cite
|
Sign up to set email alerts
|

Brivudine: A herpes virostatic with rapid antiviral activity and once-daily dosing

Abstract: Brivudine is an analog of thymidine, and is incorporated into the viral DNA. It blocks the action of DNA polymerases, thus inhibiting viral replication. It has a stronger antiviral effect against the varicella-zoster virus compared with reference compounds such as aciclovir or penciclovir. The efficacy of brivudine has been documented in a number of clinical trials in patients with herpesvirusrelated infections, particularly in patients with herpes-zoster. At a dose of 125 mg once daily, brivudine has proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…The reference drug for the treatment of immunocompromised patients presenting with VZV infections and of patients presenting with zoster is acyclovir (ACV) (7). Recently, brivudine (BVDU), another nucleoside analog, has been marketed for the treatment of varicella and zoster (15,23).…”
Section: Varicella-zoster Virus (Vzv) Is Responsible For Primary Infementioning
confidence: 99%
See 1 more Smart Citation
“…The reference drug for the treatment of immunocompromised patients presenting with VZV infections and of patients presenting with zoster is acyclovir (ACV) (7). Recently, brivudine (BVDU), another nucleoside analog, has been marketed for the treatment of varicella and zoster (15,23).…”
Section: Varicella-zoster Virus (Vzv) Is Responsible For Primary Infementioning
confidence: 99%
“…The reference drug for the treatment of immunocompromised patients presenting with VZV infections and of patients presenting with zoster is acyclovir (ACV) (7). Recently, brivudine (BVDU), another nucleoside analog, has been marketed for the treatment of varicella and zoster (15,23).We have demonstrated that several members of a new class of antivirals, the bicyclic pyrimidine nucleoside analogues (BCNAs), are highly potent and selective inhibitors of VZV in vitro (3-5, 12, 13, 16-18). This new class of compounds exhibits exclusive specificity for VZV and obligatorily requires an alkyl or alkylaryl side chain at the furan moiety for potent anti-VZV activity.…”
mentioning
confidence: 99%
“…Brivudin is a thymidine nucleoside analog with stronger antiviral effect against VZV than reference compounds such as acyclovir by blocking the action of DNA polymerases. Oral brivudin (125 mg once daily) is licensed for the treatment of HZ in several countries of the European Union ( 48 ). In a double-blind randomized multicenter study, 48 immunocompromised patients with a HZ rash less than 72 h in duration received brivudin or intravenous acyclovir treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…It is almost completely absorbed in the gastrointestinal tract after oral administration, but due to extensive first-pass metabolism, bioavailability is about 30% and extensively bound to plasma proteins (95% binding), but is not displaced by concomitant drugs, including analgesics, cardiac glycosides, cytostatics and virostatics and excreted mainly in the urine (65%) with Less than 1% of unchanged brivudine found in urine, a minor fraction has been found in the faeces (21%). The terminal half-life has been established at 16 h [1]. nt for ophthalmologic use [2].…”
Section: Introductionmentioning
confidence: 99%